Research of the Tooth Flank Design and Movement Simulation of Spiral Noncircular Bevel Gear - Xu Aifen; Jia Jumin; Chen Yuqing (Jixie chuandong)
Applied the theory of curve and surface of differential geometry,based on the noncircular bevel gear profile researched and developed successfully by research team. The construction principle of the tooth section line of the spiral noncircular bevel gear is studied. Based on the mapping method,the mathematical model of the tooth section line of the spiral noncircular bevel gear is built. On the basis of the theory and algorithm of osculating planes,the solid model of the spiral noncircular bevel gear is built. The solid model of another spiral noncircular bevel gear is built according to the enveloping principle. The correctness of the algorithm and the model is verified by the kinematics simulation results. The research results provide theoretical and technical support for the improvement and innovation of the design and meshing theory of the spiral noncircular bevel gear in the variable ratio limited slip differential.